2001
DOI: 10.1081/cbi-100103976
|View full text |Cite
|
Sign up to set email alerts
|

IMPAIRED EXPRESSION OF THEmPer2CIRCADIAN CLOCK GENE IN THE SUPRACHIASMATIC NUCLEI OF AGING MICE

Abstract: The expression of circadian clock genes was investigated in the suprachiasmatic nuclei (SCN) of young adult and old laboratory mice. Samples were taken at two time points, which corresponded to the expected maximum (circadian time 7 [CT7]) or minimum (CT21) of mPer mRNA expression. Whereas the young mice had a stable and well-synchronized circadian activity/rest cycle, the rhythms of old animals were less stable and were phase advanced. The expression of mPerl mRNA and mPer2 mRNA was rhythmic in both groups, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 11 publications
2
47
0
Order By: Relevance
“…Age-dependent changes in the circadian gene expression in laboratory rodents and humans have been described extensively. 37,38 An age-dependent difference was found in the case of Per2 mRNA expression 39 ; also Ucp2 expression increased with age. 40 Thus, the phenotype of increased CCl 4 hepatotoxicity regulated by increased Ucp2 levels because of Per2 gene deficiency could reflect the natural phenomena of increasing the sensitivity to toxicant with age in old animals.…”
Section: Discussionmentioning
confidence: 87%
“…Age-dependent changes in the circadian gene expression in laboratory rodents and humans have been described extensively. 37,38 An age-dependent difference was found in the case of Per2 mRNA expression 39 ; also Ucp2 expression increased with age. 40 Thus, the phenotype of increased CCl 4 hepatotoxicity regulated by increased Ucp2 levels because of Per2 gene deficiency could reflect the natural phenomena of increasing the sensitivity to toxicant with age in old animals.…”
Section: Discussionmentioning
confidence: 87%
“…This suggests that some age-related alterations are because of circadian system changes outside of the SCN or, alternatively, because of changes within the SCN other than the Per1 transcript that we have measured. Very recently, Weinert et al (46) reported that the amplitude of day-night expression of mPer2 but not of mPer1 in the SCN was decreased in aged mice. However, this change in mPer2 amplitude may be species-specific.…”
Section: Discussionmentioning
confidence: 99%
“…In aged animals, Per1 expression following an entraining light stimulus is markedly reduced with a significantly longer delay to resynchronization (Davidson et al, 2008;Kolker et al, 2003). In young animals, disruption of the Period genes leads to aging-like declines in sensitivity to light (Asai et al, 2001;Weinert et al, 2001). These findings suggest that temporal disorganization with advancing age may result, in part, from reductions in the sensitivity of the SCN to retinal stimulation.…”
Section: A Aged-related Changes In Circadian Entrainmentmentioning
confidence: 99%